Post-COVID-19 Longitudinally Extensive Transverse Myelitis with Myelin Oligodendrocyte Glycoprotein Antibodies. (5th April 2022) - Yang, Ellen; Husein, Adnan; Martinez-Perez, Jose; Li, Terrence
Abstract : Background . Myelin oligodendrocyte glycoprotein (MOG) antibody disease most commonly presents with optic neuritis, though myelitis is also possible. It is rare in the post-infectious and particularly post-COVID-19 setting. Case Presentation . We present the case of a 57-year-old man who tested positive for COVID-19 and experienced respiratory symptoms that completely resolved within one week. About 3 weeks after testing positive, he began experiencing acute onset anuria, followed by lower extremity paresthesia and paraparesis, which progressed to bilateral lower extremity paraplegia, complete loss of sensation of pain, temperature, vibration, and proprioception, and a T4 sensory level. He was initially diagnosed with and treated for acute inflammatory demyelinating polyradiculoneuropathy (AIDP), after which he made minimal clinical improvement. The diagnosis was shifted to longitudinally extensive transverse myelitis, and his CSF tested positive for MOG antibodies. He is being treated with a steroid regimen and extensive outpatient physical therapy. Conclusion . The neurologic manifestations of COVID-19 are still being uncovered. Neurologic symptoms should be included in patient education on symptom monitoring, even after recovery of respiratory illness, so that COVID-19-related CNS pathology can be urgently treated.